Role of Radiation Therapy Differs Between Stages in Primary Bone Large B-Cell Lymphoma in Rituximab Era: A Population-Based Analysis - Ma, Shengling; Zhang, Yuanyuan; Li, Ziying; Yan, Han; Xia, Linghui; Shi, Wei; Hu, Yu (Frontiers in Oncology, 2020)
Background: Primary bone B-cell lymphoma (PB-DLBCL) is a rare entity for which existing data is limited. Whether radiotherapy (RT) should be omitted in the modern treatment of PB-DLBCL is still under debate. We used the SEER database to compare the outcomes among adult patients treated with and without RT in rituximab era. Methods: We included adult patients with PB-DLBCL diagnosed from 2002 to 2016 from SEER 18. The effect of RT on overall survival (OS) using univariate (UVA) and multivariate (MVA) Cox proportional regression and propensity score matching (PSM) was assessed for the entire cohort and subgroups by stages. We calculated the standardized incidence ratio to estimate the short- and long-term risk for second primary malignancies (SPM) from 2002 to 2016 in SEER 18 and 1983–2016 in SEER 9. Results: A total of 1,320 patients were identified, including 856 with early-stage (ES) and 464 with advanced-stage (AS). A decreasing trend was observed in the ES cohort after 2002, while the rate of RT utilization remained stable in the AS cohort over the past three decades. Most patients in ES (63.9%) underwent RT, whereas only 42.2% of AS patients received it. RT significantly improved survival both in UVA and MVA (P < 0.001, P = 0.010, respectively). PSM analysis further validated the survival advantage of RT (P = 0.018). Moreover, a novel web-based prediction model was established to individualize the potential benefit from RT. In subgroup analyses, OS was improved with RT in those who had ES disease (p < 0.001) but not in those who had AS disease (P = 0.776). With short-term follow up in SEER 18, none of the subgroups showed a significantly elevated risk of developing SPMs. However, RT significantly elevated the late toxicities of second malignancies in ES patients diagnosed at the age of 18–39 or those with appendicular sites of bone involvement. Conclusion: This population-based analysis is the largest PB-DLBCL dataset to date and demonstrates a significant survival benefit associated with RT in early stages rather than advanced stages. In the absence of randomized controlled trials, RT should be considered in ES disease with cautions of second cancers in specific subsets of patients.